Comparative analysis of antibiotic susceptibility patterns and clinical features of mucoid and non-mucoid Pseudomonas aeruginosa infections: a retrospective study - Luo, Maoling; Li, Si; Luo, Wenying (Frontiers in Public Health, 2024)
Background: Pseudomonas aeruginosa (PA) is a prevalent opportunistic pathogen that has close associations with both acute and chronic infections. However, there exists an insufficiency of accurate and comprehensive data pertaining to the antimicrobial susceptibility patterns and clinical characteristics of both mucoid and non-mucoid strains of PA (mPA and non-mPA, respectively).From January 1, 2021, to December 31, 2022, a thorough retrospective study was carried out to examine and compare the antibiotic susceptibility test outcomes and clinical characteristics of hospitalized patients with mPA and non-mPA infections.Results: This study investigated a cohort of 111 patients who were diagnosed with mPA infections, as well as 792 patients diagnosed with non-mPA infections.Significant demographic disparities, including gender (p < 0.001), age (p < 0.001), length of hospital stay (p < 0.001), diabetes (p = 0.043), and hypertension (p < 0.001), are evident between the mPA and non-mPA groups. The mPA group commonly necessitates hospitalization for respiratory system diseases, whereas the non-mPA group is associated with concomitant cardiovascular and cerebrovascular diseases. The mPA group demonstrates lower utilization rates of medical devices, such as Foley catheter (p < 0.001), nasogastric tube (p < 0.001), mechanical ventilation (p < 0.001), tracheostomy (p < 0.001), arterial and venous catheterization (p < 0.001), and exhibits superior organ function status, including lower incidences of hypoalbuminemia (p < 0.001), septic shock (p < 0.001), liver dysfunction (p < 0.001), renal failure (p < 0.001), and respiratory failure (p < 0.001). The non-mPA group is more vulnerable to infection with two or more bacterial pathogens compared to the mPA group, with the non-mPA group frequently resulting in Enterobacteriaceae infections and the mPA group being associated with fungal infections. Variations in antibiotic sensitivity are noted for Amikacin (p < 0.001), Ciprofloxacin (p < 0.001), Cefepime (p = 0.003), and Levofloxacin (p < 0.001) in antibiotic susceptibility testing, with resistance patterns closely tied to specific antibiotic usage.2 Conclusion: There are significant demographic characteristics, clinical manifestations and antibiotic susceptibility between mPA and non-mPA infections. It is crucial to emphasize these characteristics due to their significant role in preventing and treating PA infections.